CONSUMER PROTECTION FOR VEHICLE WITHDRAWAL BY DEBT COLLECTOR IN LEASING AGREEMENTS IN WHICH CONSUMERS DEFAULT BASED ON BPSK AUTHORITY - Dliyaa Us Saabihaat (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2022)
In Indonesia, there are various forms of financial institutions, which one is leasing. In the practice of lease agreements, there are risks that can become obstacles in the implementation of the lease agreement, which are generally caused by default on the part of the lessee. The existence of a leasing agreement originates from the principle of freedom of contract which is regulated in Article 1338 of the Civil Code which states that all agreements made legally are valid as laws for those who make them. In writing this research, the researcher examines the consumer protection in an agreement made in standard, which then in its implementation creates default from one of the parties. The problem is, whether the default arising from the implementation of the agreement is a consumer violation. Consumer violations as regulated in Article 4 of Law Number 8 of 1999 concerning Consumer Protection which do not include true, clear and honest information regarding the provisions and guarantees of goods and/or services in the agreement, whether they can qualify as default, as intended in Article 52 Law Number 8 of 1999 concerning Consumer Protection regarding the duties of BPSK. The problem in this study is how to protect consumers from vehicle withdrawals by debt collectors in leasing agreements where consumers default on the authority of BPSK and what legal remedies can be taken by the consumer due to the withdrawal of vehicles by the dept collector in the leasing agreement. This study uses a normative juridical approach, data sources are obtained from statutory regulations, and literature related to the problem. In this case, consumers must be more critical and thorough in reading and understanding standard clauses such as the rights and obligations of the parties, the time the agreement is due, and the legal consequences if they cannot fulfill their obligations (default), and know that the financing agreement has already been reached. in accordance with the applicable rules.